2020
DOI: 10.1002/jhet.4094
|View full text |Cite
|
Sign up to set email alerts
|

Three‐component one‐pot synthesis of pyrazino[2,3‐a]acridine derivatives under catalyst‐free conditions

Abstract: A new series of pyrazino[2,3‐a]acridine derivatives were prepared, via three‐component reaction of quinoxalin‐6‐amine, aromatic aldehydes and 5,5‐dimethyl cyclohexane‐1,3‐dione or cyclohexane‐1,3‐dione in ethanol as a solvent at reflux. The advantages of this protocol include mild reaction conditions, easy purification, high yields, and catalyst‐free approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(28 reference statements)
0
2
0
Order By: Relevance
“… 38 Liu et al In 2020 a new series of pyrazino[2,3- a ]acridine derivatives were prepared, via three-component reaction of quinoxaline-6-amine, aromatic aldehydes, and 5,5-dimethyl cyclohexane-1,3-dione or cyclohexane-1,3-dione in ethanol as a solvent and under rehabilitation conditions. 39 In 2021, Mehrabadi et al was synthesized via preparing pistachio hull as a support followed by treatment with titanium tetrachloride (TiCl 4 ) as a nanocatalyst in a one-pot, three-component condensation reaction of aromatic aldehydes, dimedone and kojic acid in refluxing ethanol to furnish dihydropyrano[3,2- b ]chromendione derivatives. 40 In 2021, Sanai Rad et al performed a multicomponent reaction of aromatic aldehydes, aryl amines, malononitrile, and dimedone to synthesize hexahydroquinolines derivatives in the presence of a strong catalyst.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Liu et al In 2020 a new series of pyrazino[2,3- a ]acridine derivatives were prepared, via three-component reaction of quinoxaline-6-amine, aromatic aldehydes, and 5,5-dimethyl cyclohexane-1,3-dione or cyclohexane-1,3-dione in ethanol as a solvent and under rehabilitation conditions. 39 In 2021, Mehrabadi et al was synthesized via preparing pistachio hull as a support followed by treatment with titanium tetrachloride (TiCl 4 ) as a nanocatalyst in a one-pot, three-component condensation reaction of aromatic aldehydes, dimedone and kojic acid in refluxing ethanol to furnish dihydropyrano[3,2- b ]chromendione derivatives. 40 In 2021, Sanai Rad et al performed a multicomponent reaction of aromatic aldehydes, aryl amines, malononitrile, and dimedone to synthesize hexahydroquinolines derivatives in the presence of a strong catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many research groups investigated the preparation of novel nitrogen-containing heterocycles by the reaction of the amines, arylglyoxals, and nucleophilic reagents through multicomponent reactions [17][18][19][20][21][22][23]. In 2020, we developed a three-component reaction of quinoxalin-6-amine, aldehyde, and 1,3-dicarbonyl compounds in EtOH solvent, yielding pyrazino[2,3-a]acridine derivatives [24]. To continue our efforts in this project, we found that when arylglyoxal instead of arylaldehyde reacts with quinoxalin-6-amine and cyclic 1,3-dicarbonyl compound in EtOH, the reaction proceeds toward selective cyclization, resulting in pyrrolo [3,2-f]quinoxaline rather than pyrazino [2,3-a]acridine derivatives.…”
Section: Introductionmentioning
confidence: 99%